Effect of Aerobic or Resistance Exercise, or Both, on Intermuscular and Visceral Fat and Physical and Metabolic Function in Older Adults With Obesity While Dieting. Issue 1 (11th April 2021) - Waters, Debra L; Aguirre, Lina; Gurney, Burke; Sinacore, David R; Fowler, Kenneth; Gregori, Giulia; Armamento-Villareal, Reina; Qualls, Clifford; Villareal, Dennis T
Abstract: Background: Obesity exacerbates age-related effects on body composition and physical and metabolic function. Which exercise mode is most effective in mitigating these deleterious changes in dieting older adults with obesity is unknown. Methods: In a randomized controlled trial, we performed a head-to-head comparison of aerobic (AEX), resistance (REX), or combination (COMB) exercise during matched 10% weight loss in 160 obese older adults. Prespecified analyses compared 6-month changes in intermuscular adipose tissue (IMAT) and visceral adipose tissue (VAT) assessed using MRI, insulin sensitivity index (ISI) by oral glucose tolerance test, physical function using Modified Physical Performance Test (PPT), VO2peak, gait speed, and knee strength by dynamometry. Results: IMAT and VAT decreased more in COMB than AEX and REX groups (IMAT; −41% vs −28% and −23% and VAT: −36% vs −19% and −21%; p = .003 to .01); IMAT and VAT decreased in all groups more than control (between-group p < .001). ISI increased more in COMB than AEX and REX groups (86% vs 50% and 39%; p = .005 to .03). PPT improved more in COMB than AEX and REX groups, while VO2peak improved more in COMB and AEX than REX group (all p < .05). Knee strength improved more in COMB and REX than AEX group (all p < .05). Changes in IMAT and VAT correlated with PPT ( r = −0.28 and −0.39), VO2peak ( r = −0.49 and −0.52), gait speed ( r = −0.25 and −0.36), and ISI ( r = −0.49 and −0.52; all p < .05). Conclusions: Weight loss plus combination aerobic and resistance exercise was most effective in improving ectopic fat deposition and physical and metabolic function in older adults with obesity.